2001
DOI: 10.4049/jimmunol.167.12.6967
|View full text |Cite
|
Sign up to set email alerts
|

Immune Elimination ofLeishmania majorin Mice: Implications for Immune Memory, Vaccination, and Reactivation Disease

Abstract: Infection of susceptible BALB/c mice with a large, moderate, or low number of Leishmania major parasites respectively results in progressive disease, the formation of substantial but stable lesions, denoted as borderline disease, and the absence of a visible lesion. Infection with a low number of parasites results over the long term in either subclinical infections or an asymptomatic state. Subclinical mice produce a predominant Th1 response and are resistant to challenge, in contrast to their asymptomatic cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
140
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(147 citation statements)
references
References 47 publications
5
140
2
Order By: Relevance
“…However, in contrast to the resistance obtained by low-dose virulent L. major infection of BALB/c mice (6,28,29), no DTH was observed following challenge of lpg2 Ϫ mutant-infected mice, strongly suggesting that distinct mechanisms operate to maintain immunity in low-dose-and lpg2-induced resistance. Moreover, the dose of lpg2 Ϫ parasites used in these experiments would be expected to induce an IL-4 response in BALB/mice, which was not the case.…”
Section: Discussionmentioning
confidence: 48%
“…However, in contrast to the resistance obtained by low-dose virulent L. major infection of BALB/c mice (6,28,29), no DTH was observed following challenge of lpg2 Ϫ mutant-infected mice, strongly suggesting that distinct mechanisms operate to maintain immunity in low-dose-and lpg2-induced resistance. Moreover, the dose of lpg2 Ϫ parasites used in these experiments would be expected to induce an IL-4 response in BALB/mice, which was not the case.…”
Section: Discussionmentioning
confidence: 48%
“…Previous studies of CD4 ϩ and CD8 ϩ T cell memory following infection with L. major, Listeria monocytogenes, or lymphocytic choriomeningitis virus have suggested that IFN-␥-producing T EFF or T EM require persistent infection to be sustained, whereas T CM can persist in the absence of chronic infection (18,20,30,31). In contrast, the majority of virus-specific memory CD4 ϩ T cells that are maintained in sites draining the lung in the absence of Sendai virus infection have an activated phenotype (CD44 high , CD62L low ) and rapidly express IFN-␥, characteristics of T EM (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, CD4 ϩ T EFF or T EM confer more rapid protective immunity to L. major infection than T CM (20,30,31). To determine whether the CD4 ϩ T CM or T EM populations-defined by expression of CD62L-that develop following Trichuris infection differed in their ability to mediate protective immunity, purified cells from wild-type immune donors were separated into CD62L high and CD62L low fractions, labeled with CFSE, and transferred into naive congenic recipients that were subsequently infected with Trichuris.…”
Section: Central or Effector Memory Cd4 ϩ T Cells Can Mediate Immunitmentioning
confidence: 99%
“…Here we demonstrate that even before different antigen-presenting cells begin to prime adaptive immunity, the site of inoculation immediately influences the effective dose of L. major parasites that establishes infection. The parasite dose has far-reaching implications for Leishmania infections, including the nature of the adaptive immune response, and is likely one of the most important variables in determining the kinetics and outcome of infection (6,36,(44)(45)(46)(47)(48)). Our observations demonstrate that the number of parasites that establishes infection must be considered in interpreting the influence of the site of infection, as suggested previously (6).…”
Section: Discussionmentioning
confidence: 99%